Bioenergy potential of the residual microalgal biomass produced in city wastewater assessed through pyrolysis, kinetics and thermodynamics study to design algal biorefinery. (October 2019) - Shahid, Ayesha; Ishfaq, Muhammad; Ahmad, Muhammad Sajjad; Malik, Sana; Farooq, Muhammad; Hui, Zhu; Batawi, Ashwaq Hassan; Shafi, Manal Esam; Aloqbi, Akram Ahmed; Gull, Munazza; Mehmood, Muhammad Aamer
Highlights: A low-cost, contamination free, easy harvesting of microalgae was established. The lipids from the algal biomass was extracted after biochemical analyses. The residual algal biomass was pyrolyzed at four heating rates. Kinetics and thermodynamic parameters demonstrated the suitability for pyrolysis. An integrated approach of biological and thermal transformation is proposed. Abstract: The suitability of integrating biological and thermal transformation of microalgal biomass to design a biorefinery was studied. The mixed cultivation of Chlorella sp. and Bracteacoccus sp. in city wastewater produced 12 g L −1 of biomass (0.77 g L −1 day −1 ) and removed nitrates and phosphates by 68% and 75%, respectively. Microalgae outcompeted the contaminating microbes by raising the pH of wastewater to 9.93. The lipid-free residual biomass was pyrolyzed at four heating rates (10, 20, 30, 40 °C min −1 ) which showed a three-stage pyrolysis. The activation energies (182–256 kJ mol −1 ) and their corresponding lower enthalpies at the conversional fractions from 0.2 to 0.6 indicated that product formation was being favored. The values of pre-exponential factors (10 15-17 s −1 ), Gibbs free energy (159–190 kJ mol −1 ) and entropy (43–81 J mol −1 ) showed efficient pyrolysis. The data may lead to establish a robust microalgal biorefinery to produce biomass and energy along with primary treatment of city wastewater.